2021
DOI: 10.3892/mmr.2021.11972
|View full text |Cite
|
Sign up to set email alerts
|

Propofol alleviates inflammation and apoptosis in HCY‑induced HUVECs by inhibiting endoplasmic reticulum stress

Abstract: Atherosclerosis is a chronic vascular inflammatory disease, and is associated with oxidative stress and endothelial dysfunction. Homocysteine (HCY) can cause damage to endothelial cells via the enhancement of the endoplasmic reticulum stress (ERS) pathway. Propofol has a protective effect on endothelial injury and can suppress inflammation and oxidation. The purpose of the present study was to investigate the protective effect of propofol on HCY-induced inflammation and apoptosis of human umbilical vein endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Besides, we demonstrated the positive effects of propofol on antioxidant/oxidant balance with MDA, GSH, TNF-α, IL-6 levels. In various previous studies conducted, it has been shown that propofol prevents apoptosis, has anti-infl ammatory and antioxidant effects and has taken its place in the literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Based on this feature on propofol, we investigated whether it has a curative effect on neurotoxicity by developing a peripheral neurotoxicity model in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, we demonstrated the positive effects of propofol on antioxidant/oxidant balance with MDA, GSH, TNF-α, IL-6 levels. In various previous studies conducted, it has been shown that propofol prevents apoptosis, has anti-infl ammatory and antioxidant effects and has taken its place in the literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Based on this feature on propofol, we investigated whether it has a curative effect on neurotoxicity by developing a peripheral neurotoxicity model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-induced cytotoxicity is caused by oxidative stress, DNA damage, and infl ammatory cytokines [10]. When it comes to neurotoxicity, the pathophysiological mechanisms that contribute to this include infl ammation and oxidative damage as well as DNA damage and apoptotic cell death in the nervous system (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies has reported that NLRP3 can be activated through multiple pathways including NF-kb [23] ERS [24] ROS [25]and MAPK[26]. Among them, NF-KB has been widely recognized as the canonical pathway of NLRP3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis (AS) is also a severe disease that can cause vascular damage [ 120 , 121 ]. Although many drugs can treat atherosclerosis [ 122 , 123 , 124 ], their systemic administration has serious disadvantages. In particular, the proportion of therapeutic dose reaching atherosclerotic lesions is small, resulting in poor therapeutic effect.…”
Section: Mnps For Vascular Repairmentioning
confidence: 99%